Sistem Pembayaran Dan Perhitungan Pajak Parkir Di Cijerah Trade Center - Sri Mulyani; KM. Syarif Haryana (STMIK Mardira Indonesia, Bandung, 2015)
Payment systems and tax calculation parking in Cijerah Trade Center aims to simplify the payment process and the tax calculation in the management of parking in Cijerah Trade Center. This is done because processing the payment and tax calculations are still done manually which causes no problems carrying the payment of parking and difficulty in calculating taxes. System development methods by using the waterfall method. While the programming language used is Borland Delphi. Keywords: payment system; tax calculation; parking tax